Relationship of prosthesis ownership and phantom limb pain: results of a survey in 2383 limb amputees - Bekrater-Bodmann, Robin; Reinhard, Iris; Diers, Martin; Fuchs, Xaver; Flor, Herta (Pain, 2021)
Phantom limb pain (PLP) accounts for a significant reduction in quality of life and is difficult to treat. Prosthesis use has been shown to negatively covary with PLP. Recent research on body perception in amputees suggest that prosthesis ownership, defined as the extent to which a prosthesis is experienced as being part of the body rather than an artificial device foreign to the body, might interact with PLP. We used survey data from 2383 unilateral prosthesis-using upper-limb or lower-limb amputees and performed regression analyses to determine the relationship between prosthesis ownership and PLP. To test for specificity, we examined the role of prosthesis ownership also for residual limb pain (RLP) and nonpainful phantom limb sensations (npPLS). Prosthesis ownership was reduced in older participants and higher in lower-limb compared to upper-limb amputees. A longer residual limb and more frequent prosthesis use as well as a longer time since amputation also yielded higher values. Prostheses based on natural principles were associated with higher prosthesis ownership. Phantom limb pain and RLP were lower with higher prosthesis ownership, and RLP but not PLP was lower when prosthesis use was frequent. There were no significant associations for npPLS. The regression results differ in some aspects from those revealed by univariate analyses, emphasizing the importance of multivariate statistical approaches. Our findings provide insights into the interplay of body- and pain-related sensations after amputation, and could help to develop new treatment approaches for both PLP and RLP.
Gesehen am 08.12.2022